The Study of A New Hybrid Parking System in Kuala Terengganu - Yusri, Farah Nursyafiqa; Muslim, Rahmat (Progress in Engineering Application and Technology, 2021)
With the number of vehicles registered is continuously increasing in nowadays, almost of the country in the world used car as the dominant mode of transportation, thus affecting to the traffic flows and limitation for parking lots in every city and suburban area. Therefore, provision of quality services is the one of problem solving for parking facilities and management, since the parking system plays an important role in controlling the traffic flow. This study aims to assess the level of satisfaction among the public and users of parking facilities and services in Kuala Terengganu. Specifically, it focuses on aspects of frequency of using the facility, instruction signs, capacity and payment of parking facilities services. To test the hypothesis the use of automated systems in parking facilities is getting higher intention from users, an online survey of questionnaire was distributed to assess the level of satisfaction among the public and parking users in Kuala Terengganu. At the end of the analysis show most of respondent with 74% were agreed to select the horizontal system with automated movement in multi-storey parking facilities as a new parking facility to be establish. This system known as the hybrid parking system which has achieving the same result as hypothesis study based on the recommendation from the respondents. On this study, the assessment of level satisfaction among the user play an important role in development of facility in public area. Therefore, we can overcome the problems occur in the future, and help to improve the existing parking system in Kuala Terengganu.